Based On Coastal Management Policy Sustainable Development In Kenjeran Beach (Maritime Park: Journal of Maritime Technology and Society, 2022)
In the Surabaya City Spatial Plan for 2014-2030, the Kenjeran Beach area which is included in the Tambak Wedi is a marine tourism area. In recent years, the condition of the Kenjeran Beach area has experienced a decline in tourists. Given that, for several years there have been no significant changes in the development of the Kenjeran Beach area. For Kenjeran tourism to be more optimally developed, it is necessary to integrate and integrate many objects and tourist attractions in one area. The method used is the descriptive qualitative method. The results of the study describe the potential of the Kenjeran coastal area and then several policies that have been carried out by the government to develop the Kenjeran coastal area along with several impacts or conflicts on the local community. The cable car development policy for Kenjeran coastal tourism is very beneficial for the lives of coastal communities in the tourism sector and the economic life of the local community. However, the development only knocked down three fishing posts, which disturbed the people who had previously supported them. Although in the end the three posts were rebuilt in making policies, it is necessary to pay attention to no more losses on the one hand. Furthermore, the Bulak Fish Center policy whose impact is very beneficial for the survival of the Kenjeran coastal community because it is a form of livelihood so economic growth is very rapid. There are still many efforts that can be made for the implementation of policies on the Kenjeran coastal area to be more developed, but in that case, it needs to be analyzed again so that the policy is implemented properly.
Keywords: Policy, Coastal, Kenjeran Effort, Community